2013
DOI: 10.1590/s0100-69162013000600003
|View full text |Cite
|
Sign up to set email alerts
|

Initial development of two eucalyptus hybrid submitted to irrigation

Abstract: ABSTRACT:The eucalyptus offers several advantages compared to other forestry species and, by using the irrigation can increase productivity and decrease production time. The objective of the present study was to evaluate two hybrid eucalyptus (Grancam and Urograndis), no irrigation, dripping and micro sprinkler irrigated at 90, 120, 150 and 180 days after transplanting (DAT). The experiment was conducted at the experimental irrigation area in the State University of Mato Grosso do Sul, in the municipality of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Dada à rapidez da expansão das plantações no Brasil, há uma necessidade de mais informações sobre como o uso da água por estas plantações variam de acordo com a produtividade florestal, bem como a intensidade de manejo (HUBARD et al, 2010). Oliveira et al (2013) estudando a aplicação de água por diferentes sistemas de irrigação, evidenciaram que nos estádios iniciais do desenvolvimento do eucalipto o conteúdo de água no solo proporcionou maior altura de planta e volume de madeira quando comparado com cultivo de sequeiro. Segundo Seghatoleslami, Kafi e Majidi (2008), o solo com baixa disponibilidade de água pode causar estresse por deficiência hídrica que é um dos principais fatores que reduz o crescimento e o desenvolvimento de plantas, sendo que as reações das plantas a esse fator diferem significantemente em vários níveis organizacionais, dependendo, principalmente, da intensidade e duração do estresse bem como da espécie e do estádio de crescimento da planta (JALEEL et al, 2008).…”
Section: Introductionunclassified
“…Dada à rapidez da expansão das plantações no Brasil, há uma necessidade de mais informações sobre como o uso da água por estas plantações variam de acordo com a produtividade florestal, bem como a intensidade de manejo (HUBARD et al, 2010). Oliveira et al (2013) estudando a aplicação de água por diferentes sistemas de irrigação, evidenciaram que nos estádios iniciais do desenvolvimento do eucalipto o conteúdo de água no solo proporcionou maior altura de planta e volume de madeira quando comparado com cultivo de sequeiro. Segundo Seghatoleslami, Kafi e Majidi (2008), o solo com baixa disponibilidade de água pode causar estresse por deficiência hídrica que é um dos principais fatores que reduz o crescimento e o desenvolvimento de plantas, sendo que as reações das plantas a esse fator diferem significantemente em vários níveis organizacionais, dependendo, principalmente, da intensidade e duração do estresse bem como da espécie e do estádio de crescimento da planta (JALEEL et al, 2008).…”
Section: Introductionunclassified
“…This may be related to a better interaction of genotype with the environment, enabling greater height of this hybrid. Oliveira et al (2013), evaluating the same hybrids, also observed greater height values for the Grancam hybrid. The authors claim that this parameter is strongly linked to genetic character.…”
Section: Discussionmentioning
confidence: 70%
“…Similar results were observed by Fernandes et al (2012) and Vellini et al (2008), which verified higher values of plant height and stem diameter for the irrigated treatments, and Reis et al (2006), which reported having found higher values of wood volume. In addition, Oliveira et al (2013), studying the application of water by different irrigation systems, showed that the water content in the soil provided higher plant height and wood volume in the initial stages of eucalyptus growth when compared to the dry farming.…”
Section: Introductionmentioning
confidence: 99%